The use of mobile-assisted language learning (MALL) for english in agricultural education - Imam Suhaimi; Futika Permatasari; Muhammad Fawaid (Dharma Pendidikan, 2025)
Mobile-Assisted Language Learning (MALL) has become increasingly relevant for English language instruction, particularly in English for Specific Purposes (ESP) within the agricultural field. This study aimed to evaluate the effectiveness of MALL in enhancing technical vocabulary mastery, speaking skills, and students’ perceptions of its ease of use and usefulness. A non-equivalent quasi-experimental design with pretest–posttest and control group was applied, involving 60 students from the Faculty of Agriculture and Animal Husbandry at Universitas Kahuripan Kediri over a six-week intervention period. ANCOVA analysis revealed that the MALL group showed a significant increase in vocabulary scores (M = 31.2) compared to the control group (M = 27.9), F(1,57) = 7.21, p = .009, with a moderate-to-strong effect size (d ≈ 0.66). Speaking skills also improved significantly, with the MALL group (M = 3.38) outperforming the control group (M = 3.05), F(1,57) = 6.02, p = .017. Furthermore, students reported positive perceptions of MALL’s usability and value. These findings provide empirical evidence that MALL strengthens cognitive, affective, and engagement aspects of language learning. This study highlights MALL’s potential as an adaptive and contextual approach for agricultural ESP learning and offers practical implications for curriculum development and pedagogical innovation in the digital era.